Peningkatan kemampuan menyelesaikan soal cerita pecahan melalui model team assisted individualization (tai) pada siswa kelas v sekolah dasar - Nahdiya Mufti Attika; Rukayah Rukayah; Idam Ragil Widianto Atmojo (Universitas Sebelas Maret, 2021)
This research aims to improve solving problem ability about fraction for the fifth grade students using Team Assisted Individualization (TAI). The subject of this research were 18 students of the fifth grade of SD Negeri 01 Mesoyi. This research is Classroom Action Research conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection. In the 1st cycle improved precycle from 55,72 to 72,22 for the classical completeness. The classical completeness percentage improved from 22,22% to 66,67% in 1st cycle.. The results of the 2nd cycle after was fixed from the the 1st cycle shows that the average of the ability to solve essay problem of fraction was higher. The average score improve from 77,22 to 76,77 in the 2nd cycle. The classical completeness of the cycle 1st to 2nd is 66,67% to 83,33%. The conclusion from this research shows that using Team Assisted Individualization can improve the ability to solve essay problem of fraction for the fifth grade of 01 Mesoyi elementary school Talun Distric Pekalongan Regency in the academic year 2020/2021